ثنائية (اليوتوبيا – الديستوبيا) في الرواية العراقية دراسة سيميائية - Nasser, Ahmed Abdul Razzaq (Al-Adab Journal, 2015)
This study aims to bring to light the contrary binary (Utopia- Dystopia), which played a thematic role in three Iraqi novels, published after 2003: (Few Air) for the novelist Jinan Jasim Hillawy, (Star of AL- Battaween) for the writer Shakir AL- Anbari And (The Pomegranate Alone) for the writer Sinan Antoon. We will focus on the Semantic structure, by using the technique of Semiotic Square, which introduced by Paris School Semiotics, especially her pioneer Greimas. This Study try to answer this question: Were Iraqi cities represent a utopian cities before 9 April 2003, and then became a dystopian cities after invasion of Iraq? It is worth mentioning, the focusing on the theme of Dystopia in Iraqi and Arabic novels, has been overlooked from many modern narrative studies.